Effect of Soybean Biodiesel Addition on the Quality of Palm Stearin Biodiesel - Joelianingsih Joelianingsih; Yuli Amalia Husnil; Is Sulistyati Purwaningsih (International Journal of Oil Palm, 2018)
Cold flow properties and oxidation stability are two important biodiesel characteristics. Usually biodiesel has these two properties in opposing qualities. Palm stearin biodiesel contains high levels of saturated fatty acid methyl esters (FAME) in the form of 63% palmitic acid methyl ester. Thus this type of biodiesel has bad cold flow properties and good oxidation stability. On the other hand, soybean biodiesel has a high level of unsaturated FAME in the form of 53% linoleic acid methyl ester. Hence it has good cold flow properties whereas the oxidation stability is bad. According to SNI 7182:2015 the maximum temperature of cloud point is 18 °C and minimum value for oxidation stability is 8 hours. The cloud point of palm stearin biodiesel (PSB) can be lowered to below 18 °C, while keeping the oxidation stability at 8 hours, by blending it with soybean biodiesel (SB). In this experiment, cold flow properties and oxidation stability of PSB are 17.4 °C and 17 hours respectively while for the cold flow properties of SB are 0.8 °C and oxidation stability 4.5 hours. The blending was done continuously for 15 minutes with variations in PSB/SB mass ratio 97.5:2.5, 95:5, 92.5:7.5 and 90:10. The cloud point and oxidation stability were analyzed using ASTM D 5773 and EN 15751 respectively. The results showed that by lowering the mass fraction of PSB, the biodiesel blend would have lower values for cloud point while still having good properties in term of oxidation stability. In this study the PSB/SB ratio that resulted in the lowest cold flow property i.e. 16.8 °C was 90:10 with 8.53 hours of oxidation stability